Impact of hybrid steel fibres on fresh and mechanical properties of Self-compacting concrete. (December 2022) - K.B., Ramkumar; P.R., Kannan Rajkumar
Abstract: Fibre-reinforced concrete is increasingly employed in construction in recent times. Adding steel fibres to self-compacting concrete (SCC) increases the latter's strength and toughness but does not confer the SCC mix with the desired flow properties. When more than one type of fibres is added to the concrete mix in appropriate proportions, its mechanical properties improve. Research on the impact of hybrid fibres on concrete's mechanical properties is sparse. Therefore, in this paper, the workability of high-flowable 60 and 80 MPa SCC prepared using hybrid steel fibres is studied. The experimental results are then compared with the output obtained from the regression model that was developed. We found that the addition of 0.40 % and 0.10 % of hybrid hooked and micro-steel fibres improves the performance of the fresh and hardened concrete. The values for split tensile, flexural strength and elastic modulus in the regression model developed were found to be in consonance with their experimental values. Graphical Abstract: ga1